Role of cross-cultural communicatin in tourism and maintenance of tourist education and science - Smorzhok I. P. (Interactive science, 2016)
this article descusses cross-cultural communication problems, determines the ways to solve them, proves the role of cross-cultural communication in tourism, touristic education and science.
Keywords: образование; культура; народы; туризм; наука; science; education; Tourism; culture; межкультурные коммуникации; nations; cross-cultural communication